Banking service quality perceived by students: Implications to green services - Đokić Nenad; Milićević Nikola; Kalaš Branimir; Đokić Ines (Strategic Management)
Background: The paper examines banking service quality perceived by students as a basis for determining implications for green services. The focus was on this market segment bearing in mind its potential effects on banks' long-term profitability and students' acquaintance with environmental issues. The attention was dedicated to the green banking concept taking into account the role which banks have in creating an eco-friendly society. Purpose: The aim of the research refers to identifying banking service quality aspects that are important for students. Later, those can be used as a starting point in determining actions regarding green services in the case of the student population. Study design/methodology/approach: The quality of a bank service was modeled as a hierarchical reflective-formative construct, because of which the SmartPLS software was applied. Five SERVQUAL dimensions (assurance, empathy, reliability, responsiveness, and tangibles) were specified as lower-order reflective constructs which form the higher-order formative construct (banking service quality). After testing the model, separately for reflective and formative constructs, path coefficients were presented. Finding/conclusions: The results have shown that responsiveness and assurance represent dimensions that have the largest contribution to banking service quality, i.e. the highest path coefficients to higher-order construct. In accordance with those findings, certain implications concerning green services were given. Limitations/future research: The omission of certain variables that may be related to banking services represents the limitation of this study; hereby, in future researches, some socio-demographic characteristics (such as gender, household income, etc.) could be included in the analysis.